A precambrian proximal ejecta blanket from Scotland - Amor, K; Hesselbo, S; Porcelli, D; Thackrey, S; Parnell, J (Geological Society of America, 2008)
Ejecta blankets around impact craters are rarely preserved on Earth. Although impact craters are ubiquitous on solid bodies throughout the solar system, on Earth they are rapidly effaced, and few records exist of the processes that occur during emplacement of ejecta. The Stac Fada Member of the Precambrian Stoer Group in Scotland has previously been described as volcanic in origin. However, shocked quartz and biotite provide evidence for high-pressure shock metamorphism, while chromium isotope values and elevated abundances of platinum group metals and siderophile elements indicate addition of meteoritic material. Thus, the unit is reinterpreted here as having an impact origin. The ejecta blanket reaches >20 m in thickness and contains abundant dark green, vesicular, devitrified glass fragments. Field observations suggest that the deposit was emplaced as a single fluidized flow that formed as a result of an impact into water-saturated sedimentary strata. The continental geological setting and presence of groundwater make this deposit an analogue for Martian fluidized ejecta blankets.